Microdynamics of perceptual trustworthiness in perception of facial expressions - D.A. Diveev; A.A. Demidov (Экспериментальная психология, 2015)
The article discusses the phenomenon of «perceptual trust» and its formation in micro intervals of time. The results of two empirical studies of trust’s perceptual estimates by human faces in various aspects of time exposure was revealed. In the first study, the following values of the time exposure used: 100,250 and 1000 ms. It is shown that the value for adequacy of perceptual trust are the highest exposure at 250 ms, and the least at 1000 ms. It is suggested that the evaluation of perceptual trust depends not only on the time of the demonstration of human facial expressions, sex, but also on the expression of human face. Wider range of exposure time values was used in the second study, 100, 300, 500, 1000 and 3000 to 1000 ms. As of stimulus images were made by representatives of persons Caucasoid, Mongoloid and Negroid racial groups. As the subjects were made by representatives of the Mongoloid racial group. The relationship between the adequacy of the perceptual trust evaluations and race of subjects and models are tested and evaluated models was revealed. The main result of the research can be considered a lack of empirical fixation unambiguous relationship between the level of trust in the person being evaluated and the duration of the perception of his face.